PENGELOLAAN PERPUSTAKAAN DIPODRONO UNTUK MENINGKATKAN LITERASI SISWA DI MADRASAH TSANAWIYAH DIPODRONO - Fauzia, Farida Sifak; Amin, Muhammad; Aula, Fikarimatil; Aniqoh, Aniqoh (Institut Agama Islam Syubbanul Wathon Magelang, 2025)
School library management plays a central role in enhancing student literacy at the Madrasah Tsanawiyah (MTs) level. This community service program aims to optimize the Dipodrono Library as a learning resource center through the Asset-Based Community Development (ABCD) approach. Unlike conventional assistance, this program focuses on mobilizing internal assets, including the competence of administrative staff, student creativity as literacy mobilizers, and unorganized donated book collections. The program followed the 5D cycle: Discovery, Dream, Define, Design, and Destiny. The results show that systematic library management—including collection classification, aesthetic revitalization of the reading area, and the activation of borrow-and-read programs—successfully increased the average daily student visits by 60%. Synergy in leveraging madrasah assets has proven effective in transforming the library from a mere book storage room into an active and sustainable literacy ecosystem.